Cost Allocation of Reactive Power Using Matrix Methodology in Transmission Network - Gaurav Gupta; Manisha Dubey; Anoop Ayra (International Journal of Advances in Applied Sciences, 2018)
In the deregulated market environment as generation, transmission and distribution are separate entities; reactive power flow in transmission lines is a question of great importance. Due to inductive load characteristic, reactive power is inherently flowing in transmission line. Hence under restructured market this reactive power allocation is necessary. In this work authors presents a power flow tracing based allocation method for reactive power to loads. MVAr-mile method is used for allocation of reactive power cost. A sample 6 bus and IEEE 14 bus system is used for showing the feasibility of developed method.